2003
DOI: 10.1242/jcs.00778
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of extracellular matrix remodeling by the first type III repeat in fibronectin

Abstract: The fibronectin matrix contains cryptic sites which are thought to modulate cellular biological responses. One of these sites, located in fibronectin's first type III repeat (III1c), influences signaling pathways that are relevant to cytoskeletal organization and cell cycle progression. The purpose of this study was to identify possible mechanisms responsible for the effects of III1c on cell behavior. Recombinant peptides representing various type III repeats of fibronectin were compared for their effects on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 73 publications
1
57
0
Order By: Relevance
“…Our analysis identifies the segment III (20). This epitope loss was originally interpreted as remodeling of the matrix.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our analysis identifies the segment III (20). This epitope loss was originally interpreted as remodeling of the matrix.…”
Section: Discussionmentioning
confidence: 94%
“…Although a high concentration of imidazole was used for elution, anastellin was spread out over a large number of fractions and had to be concentrated with a Centricon-10 (Millipore) as described previously (19). Anastellin (with a His 6 tag) from the pQE-70 vector (20) was also recloned into pET11b for expression in BL21(DE3) to improve solubility. However, the majority of anastellin was still insoluble and required renaturation.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of the Recombinant Fibronectin Modules-All recombinant His-tagged fibronectin modules, III-1c, III-13, and III-10n, were prepared and purified as described previously (13,17,18). Briefly, PCR products were obtained by amplification of human fibronectin cDNA and cloned into bacterial expression vectors pQE-70 (III-1c and III-13) and pQE-30 (III-10n) in-frame with a bacterial His 6 tag (Qiagen, Inc., Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The cryptic polymerization activity present in the III 1 domain of fibronectin can be recapitulated in a peptide termed anastellin (Morla et al, 1994;Morla and Ruoslahti, 1992). Subsequent studies showed that anastellin can bind directly to previously assembled fibronectin matrix and alter its conformation (Klein et al, 2003;Prabhakaran et al, 2009). Anastellin has been found to inhibit tumor angiogenesis in vivo as well as endothelial cell proliferation in vitro; however, its mechanism of action has remained elusive (Ambesi et al, 2005;Yi and Ruoslahti, 2001).…”
Section: Introductionmentioning
confidence: 99%